Unveiling Patient Satisfaction: Analysis of Factor Influencing Patient-Centered Care At Bunda Margonda Hospital - Putra, Putu Agus Sujana; Susanti, NLP Dina; Rismawan, Made; Kusuma, Made Dian Shanti (Babali Publisher, 2025)
Introduction: The Patient-Centered Care (PCC) model aims to improve the quality of healthcare services by upholding human dignity and recognizing each patient’s individuality, regardless of nationality, ethnicity, skin color, age, gender, political beliefs, religion, or social status. This study aimed to identify key factors influencing patient satisfaction with healthcare services based on PCC principles, specifically comparing patients with BPJS and non-BPJS payment statuses.Methods: This quantitative study employed a cross-sectional design. A total of 315 respondents who had been hospitalized for more than 24 hours at Bunda Margonda Hospital were selected through convenience sampling. Data were collected using the PPE-15 questionnaire and analyzed using descriptive statistics, Chi-square tests, and logistic regression.Results: Among BPJS patients, satisfaction was significantly influenced by gender (p = 0.029), marital status (p = 0.023), education (p = 0.020), and length of treatment (p = 0.025). In the non-BPJS group, age (p = 0.029) and marital status (p = 0.024) were significant factors. Logistic regression analysis revealed that length of stay was the most influential factor for BPJS patients (aOR = 2.3; p = 0.023), whereas marital status was the primary factor for non-BPJS patients (aOR = 1.3; p = 0.024).Conclusion: A shorter length of hospital stay is positively associated with higher satisfaction among BPJS patients, while marital status significantly influences satisfaction among non-BPJS patients. These findings highlight the need for tailored approaches in delivering patient-centered care based on payment status and demographic characteristics.